Circadian Clock and Liver Cancer - Crespo, María (Cancers (Basel), 2021)
SIMPLE SUMMARY: The circadian coordination of metabolism is tightly regulated, and its alteration can trigger several diseases, including liver steatohepatitis and cancer. Many factors (such as diet and jet lag) shape both the liver molecular clock and the circadian transcription/translation of genes related to different metabolic pathways. Here, we summarize our current knowledge about the molecular mechanisms that control this circadian regulation of liver metabolism. ABSTRACT: Circadian clocks control several homeostatic processes in mammals through internal molecular mechanisms. Chronic perturbation of circadian rhythms is associated with metabolic diseases and increased cancer risk, including liver cancer. The hepatic physiology follows a daily rhythm, driven by clock genes that control the expression of several proteins involved in distinct metabolic pathways. Alteration of the liver clock results in metabolic disorders, such as non-alcoholic fatty liver diseases (NAFLD) and impaired glucose metabolism, that can trigger the activation of oncogenic pathways, inducing spontaneous hepatocarcinoma (HCC). In this review, we provide an overview of the role of the liver clock in the metabolic and oncogenic changes that lead to HCC and discuss new potentially useful targets for prevention and management of HCC.